Wafer-scale very large memory windows in graphene monolayer/HfZrO ferroelectric capacitors. (17th August 2018) - Dragoman, Mircea; Modreanu, Mircea; Povey, Ian M; Dinescu, Adrian; Dragoman, Daniela; Di Donato, Andreea; Pavoni, Eleonora; Farina, Marco
Abstract: We have fabricated and electrically characterized at the wafer scale tens of metal-ferroelectric (HfZrO)-semiconductor capacitors and metal-graphene monolayer-ferroelectric (HfZrO)-semiconductor capacitors with the same top electrode dimensions. We have found that the memory windows of the capacitors containing graphene are 3–4 times larger than the ferroelectric capacitors without graphene, and increase even more after annealing. This physical effect can be attributed to the additional electric field exerted by the graphene monolayer on the HfZrO ferroelectric semiconductor capacitor, and to the negative thermal extension coefficient of graphene, respectively.